TRADITION OF THE VILLAGE REPORT OF SENOYAN MARGOYOSO PATI - Taqiyyuddin, Muhammad Imam; Faza, Najwa Zakial; Falaq, Yusuf (JURNAL SOCIUS, 2025)
Local traditions are a form of cultural wisdom that still lives in rural communities in Indonesia, one of which is the Lamporan tradition in Soneyan Village, Margoyoso District, Pati Regency, Central Java. This tradition is carried out every Friday in the month of Suro and is believed to be a form of protection from disturbances by spirits. This study aims to identify the symbolic meaning, social function, and role of the Lamporan tradition in the lives of modern society. The method used is a qualitative approach with participatory observation techniques and in-depth interviews with community leaders and tradition practitioners. The results of the study show that Lamporan not only functions as a spiritual effort to ward off disaster, but also strengthens social solidarity, maintains cultural identity, and becomes a medium for transmitting ancestral values to the younger generation. In the midst of modernization, this tradition continues to exist because of the active role of the community in preserving cultural heritage. This study contributes to the understanding of the preservation of local traditions in facing contemporary social dynamics.